The impact of listening strategy instruction on English-Majored sophomores' listening comprehension at Soc Trang community college : - Nguyễn, Văn Tâm (Can Tho University, 2008)
In an attempt to improve the quality of listening instruction, the researcher conducted this experimental study to determine the impact of listening strategy instruction on English-majored sophomores' listening comprehension at Soc Trang Community College.